Management Patient of Swine Influenza - Gunawan, Endra; Nasronudin, Nasronudin (Institute of Topical Disease, 2015)
Influenza is an acute respiratory diseases caused by various influenza virus which infect the upper and lower respiratory tract and often accompanied by systemic symptoms such as fever, headache and muscle pain. Influenza spreads through the air. Swine influenza comes from swine and can cause an outbreaks in pig flocks. Even this is a kind of a rare case but the swine influenza could betransmitted to human by direct contact with infected swine or through environment that already being contaminated by swine influenza virus. There are 3 types of swine influenza virus namely H1N1, H3N2 and H1N2. Type H1N1 swine-virus had been known since 1918. Avian influenza virus infection is transmitted from one person to another through secret containing virus. Virus is binded into the mucous cells of respiratory tract before it is finally infecting the cells itself. Management patients with H1N1 influenza is based on the complications and the risk. Besides, it is also need to consider the clinical criteria of the patient. Therapy medicamentosa is applied to the patients by giving an antiviral, antibiotics and symptomatic therapy. Prevention can be done by avoid contact with infected animal or environment, having antiviral prophylaxis and vaccination.